ANALYSIS OF CHINA'S REJECTION OF THE PERMANENT COURT OF ARBITRATION RULING IN THE SOUTH CHINA SEA DISPUTE - Eliezer, Theofillus; Hakim, Naufal Rafi; Amir, Danial; Budianto, Jeremy (Tirtayasa Journal of International Law, 2024)
The Philippines filed a case against China at the Permanent Court of Arbitration (PCA) in 2013. The case concerned territorial disputes in the South China Sea, particularly China’s territorial claims over nearly the entire region. The PCA issued a ruling in 2016 rejecting China’s claims, referencing Annex VII Article 11 of the 1982 UNCLOS, which states that PCA decisions are final and binding. However, China rejected the PCA ruling for several reasons. The purpose of this research is to examine the reasons behind China's rejection of the PCA ruling and the consequences of this rejection. The research employs a normative juridical method focusing primarily on legal materials, as it considers legal rules of a normative nature. The data used in this study is secondary data. China rejected the PCA ruling for several reasons: first, China considered the decision invalid because they never consented to the arbitration process initiated by the Philippines. Second, China argued that the PCA lacked jurisdiction to adjudicate the dispute. China's rejection of the PCA ruling highlights the weaknesses of international law and poses potential threats to sovereignty and security in the ASEAN region, including opening opportunities for illegal activities in the South China Sea.